Hydrothermal synthesis of double sheaf-like Sb2S3 using copolymer as a crystal splitting agent - Chalermchai Pilapong (2018)
Double-sheaves of antimony sulfide were synthesized by the 200 °C and 24 h hydrothermal reaction in the acidic solution, containing copolymer - a crystal splitting agent. Using X-ray technique, electron microscopy, and Raman as well as UV-visible NIR absorption spectroscopy, the products were specified as orthorhombic Sb2S3, composing of Sb and S with five vibration modes, in the shape of spears in bundles with the [0 0 1] growth direction and 2.38 eV direct energy gap. A diffraction pattern was also simulated, and is in good accordance with that obtained by the interpretation. © 2010 Elsevier B.V. All rights reserved.